2008
DOI: 10.1007/s00198-008-0810-0
|View full text |Cite
|
Sign up to set email alerts
|

Bone mass and structure in adolescents with type 1 diabetes compared to healthy peers

Abstract: In conclusion, type 1 diabetes is associated with reduced BMC and appears to affect bone cross-sectional size and cortical rigidity. The diabetes-related skeletal deficits seemed to concern male adolescents more than females. Whether diabetes-related deficits would contribute to an increased risk of fractures in adulthood or later in life remains to be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
70
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 33 publications
(44 reference statements)
12
70
1
6
Order By: Relevance
“…A negative influence of type 1 diabetes on bone has been observed in a number of case-control studies conducted in adults [2,22] as well as in children and adolescents [1,4,6,[23][24][25], where peripheral and axial DXA and QCT were employed. It has been suggested that observed differences in adults may result from mineralisation disorders, which operate during rapid skeletal development in puberty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A negative influence of type 1 diabetes on bone has been observed in a number of case-control studies conducted in adults [2,22] as well as in children and adolescents [1,4,6,[23][24][25], where peripheral and axial DXA and QCT were employed. It has been suggested that observed differences in adults may result from mineralisation disorders, which operate during rapid skeletal development in puberty.…”
Section: Discussionmentioning
confidence: 99%
“…In adults with type 1 diabetes, studies based on measurements at different skeletal sites have shown decreased bone mineral density (BMD) [1,2]. The results and causative factors related to the hypothesised bone mineralisation diminution and bone disturbance in children and adolescents are more equivocal [3][4][5][6][7][8][9]. In adolescents with type 1 diabetes the influence of unsatisfactory metabolic control [1,7,8], disease duration [6][7][8] and high insulin requirement [9] have been postulated.…”
Section: Introductionmentioning
confidence: 99%
“…Some (45,56) have reported no difference in the BMD between diabetics and controls, whereas others (51,52,53,54,55,57) have documented a decrease in either trabecular and/or cortical BMD at these sites. F/M, female/male; Duration, duration of diabetes in years; Site, skeletal site demonstrating a decreased bone mineral density (BMD); MVC, correlation between BMD and diabetic microvascular complication(s); GC, correlation between BMD and glycaemic control (usually the mean HbA1c); NR, not reported; H, hip; S, spine; TB, total body; Hip*, only site measured; Spine*, only site measured.…”
Section: Quantitative and Structural Bases Of Bone Fragilitymentioning
confidence: 99%
“…A number of studies have documented a smaller crosssectional radial or tibial bone area in T1DM compared to controls (51,56,57), especially during childhood (57,64), but with a normalization with age (65), and reported an association between glycaemic control and decreased bone size (52,54).…”
Section: Bone Size and Microstructurementioning
confidence: 99%
See 1 more Smart Citation